Mechanical behaviour of additive manufactured 316L f2ccz lattice structure under static and cyclic loading. (May 2020) - Ashouri, D.; Voshage, M.; Burkamp, K.; Kunz, J.; Bezold, A.; Schleifenbaum, J.H.; Broeckmann, C.
Abstract: Additive Manufacturing (AM) provides new freedom of constructive possibilities for design engineers. Many structures with features like cavities or thin beams are difficult to be manufactured using conventional methods such as casting or machining while AM can ease this difficulty. Nevertheless, the various parameters that can influence the fatigue and structural behavior of the AM metals should not be neglected. So far, there are only a few studies on the influence of process parameters on the failure of lattice structures under fatigue loading. For this perspective, this article presents the manufacturing of lattice structures, and investigates basic failure mechanisms at the meso and macro levels. Within this framework, the process parameters of Laser-Powder Bed Fusion (L-PBF) are initially varied in order to influence the structure and to set it in a targeted manner. The varied process parameters are three different laser powers with adjusted speeds, which are applied to the additively manufactured samples. Static bending and cyclic axial loading are performed to investigate the mechanical strength of the specimens.